2020
DOI: 10.17853/1994-5639-2019-10-9-31
|View full text |Cite
|
Sign up to set email alerts
|

International academic mobility through the prism of soft power theory

Abstract: Introduction. In the era of globalisation and digitalisation of society, the phenomenon of mobility is of particular relevance in the humanitarian discourse. Technological, socio-political and economic changes, penetrating into the sectors of education and science, contribute to internationalisation, intensification, as well as the inclusive growth of these priority areas of society. The study of academic mobility in the context of the theory of soft power will make it possible quantitatively measure and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Hirsch [31] proposed the h-index, which is superior to other indicators in predicting future scientific achievement. Kovba and Gribovod [32] found that the academic strength of an institution is often reflected in the international academic mobility preferences of students. Therefore, in this study, the academic impact (outcome variable) was measured using the international student ratio, international collaborations, network of scientific papers, documents in the top 1%, citation impact, frequently cited papers, and H-Index.…”
Section: Datamentioning
confidence: 99%
“…Hirsch [31] proposed the h-index, which is superior to other indicators in predicting future scientific achievement. Kovba and Gribovod [32] found that the academic strength of an institution is often reflected in the international academic mobility preferences of students. Therefore, in this study, the academic impact (outcome variable) was measured using the international student ratio, international collaborations, network of scientific papers, documents in the top 1%, citation impact, frequently cited papers, and H-Index.…”
Section: Datamentioning
confidence: 99%
“…Высокий уровень инклюзии -важная позитивная особенность виртуальной академической мобильности. Однако активному развитию международной виртуальной академической мобильности препятствует ряд факторов: недостаточность материально-технической базы и нехватка кадров для реализации виртуальных форм обучения; языковой барьер; нормативно-правовой вопрос -признание международных дипломов, полученных в результате дистанционного и сетевого обучения, работодателем и заинтересованными организациями [12].…”
Section: трансформации института академической мобильностиunclassified
“…and Gribovod E.G. consider international academic mobility as a resource of "soft power" in the context of the digitalization and globalization of higher education [8]; Macek A. and Ritonija N., as well as Petrova L.E., Kuzmin K.V. reveal the possibilities of virtual mobility and network learning [10,18].…”
Section: Peculiarities Of Digitalization Analysis In the Academic Sciencementioning
confidence: 99%